Design of organ-on-a-chip to improve cell capture efficiency. (1st November 2021) - Yang, Qingzhen; Ju, Dapeng; Liu, Yan; Lv, Xuemeng; Xiao, Zhanfeng; Gao, Bin; Song, Fenhong; Xu, Feng
Highlights: An Euler-Lagrange numerical model is developed to simulate the particulate flow. The flow field and the dynamic process of cell capture in organ-on-a-chip are obtained. Different designed chips are studied to evaluate the cell capture efficiency. Experiments are conducted to validate the simulation results. Abstract: Organ-on-a-chip has emerged as a powerful platform with widespread applications in biomedical fields. In this platform, living cells are cultured in microfluidic chips to mimic the functions of native organ units in vitro . One important step for organ-on-a-chip is to capture cells, thus some microstructures are usually integrated in the chip to trap cells when the suspension is ejected into chip. To predict and evaluate the cell capture efficiency, we developed an Euler-Lagrange numerical model to simulate the dynamic process of cell capture. In this model, the Stokes equation was employed to solve the flow field with cells considered as spherical particles. The capture efficiency was quantified in terms of the number of trapped cells and the uniformity. Employing this model, the performance of three different designed chips was studied by numerical simulations and compared with experiments. This numerical model could be used to optimize the design of organ-on-a-chip. Graphical abstract: Image, graphical abstract